2009
DOI: 10.1016/j.sleep.2008.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Sleep deprivation worsens inflammation and delays recovery in a mouse model of colitis

Abstract: Background and aim We recently showed that patients with inflammatory bowel disease (IBD) report significantly more sleep disturbances. To determine whether disrupted sleep can affect the severity of inflammation and the course of IBD, we used an animal model of colonic inflammation to determine the effects of acute and chronic intermittent sleep deprivation on the severity of colonic inflammation and tissue damage in colitis and recovery from this damage. Methods Acute sleep deprivation (ASD) consisted of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
76
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(79 citation statements)
references
References 36 publications
2
76
0
1
Order By: Relevance
“…A recent experimental study using an animal model of colitis found that acute and intermittent sleep deprivation patterns aggravated inflammation and slowed recovery, with some evidence of a 'dose' response. 15 Stress has been found to alter the release of pro-inflammatory mediators, and increase intestinal permeability, which can contribute to intestinal inflammation. 47 Finally, a novel communication pathway between the immune system and the brain has been described, 48 suggesting that inflammation in chronic disease may cause fatigue through monocyte infiltration in the brain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent experimental study using an animal model of colitis found that acute and intermittent sleep deprivation patterns aggravated inflammation and slowed recovery, with some evidence of a 'dose' response. 15 Stress has been found to alter the release of pro-inflammatory mediators, and increase intestinal permeability, which can contribute to intestinal inflammation. 47 Finally, a novel communication pathway between the immune system and the brain has been described, 48 suggesting that inflammation in chronic disease may cause fatigue through monocyte infiltration in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…13 Sleep disturbances have been associated with exacerbation of symptoms such as pain and fatigue in multiple chronic inflammatory conditions as well as worsening disease course. 14,15 Studies on fatigue in IBD have primarily relied on smaller samples (n<100), tertiary clinic recruitment, and patients with IBD in remission, 6,16 thereby considering only part of the spectrum of IBD presentation. The aim of this study was to evaluate fatigue and its related parameters more comprehensively, considering sleep quality, psychological factors, and biological indicators of inflammation and serum hemoglobin (Hg) levels simultaneously, in order to clarify their presentation and relationships in IBD.…”
Section: Introductionmentioning
confidence: 99%
“…40 There is further evidence that sleep deprivation may increase gastrointestinal symptom activity. 40,41 A possible explanation for this finding may be that altered sleep is an indication of increasing disease activity. Indeed, IBD patients have reported in previous studies to relate their disturbed sleep with disease activity.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 SF by itself can also induce activation of inflammatory mechanisms, more specifically tumor necrosis factor (TNF)-α-dependent pathways, which propagate the engagement of the innate immune system. 14,15 Polysomnographic studies have revealed profound sleep disruption in ICU patients with decreases in total sleep time, altered sleep architecture, and severe SF. 16,17 We posited that the combination of SF and surgery would enhance the neuroinflammatory response produced either alone or that the combination results in exacerbated cognitive impairment.…”
mentioning
confidence: 99%